Are pandemics associated with intensive livestock production? - Alvseike Ole; Tollersrud Tore; Blagojević Bojan (Veterinarski Glasnik, 2021)
Covid-19 has awakened the world to the importance of infectious diseases. However, it also affected several people, including researchers, as well as some organizations to blame the pandemic on intensive livestock production. Several factors contribute to the fact that the next pandemic is less likely to come from intensive livestock farming than from wild animals and traditional small-scale livestock production. However, there are also the facts that support the role of intensive production in spreading of diseases. One Health - the interaction between the health of humans, animals and the environment has received a lot of attention. Livestock production plays a role in these interactions, but is not a primary driver for the development of new pandemics.